Литовская топонимика и грамматические нормы русского языка - Синочкина, Б. М. (Kalbotyra, 1990)
The paper deals with the problem of some Lithuanian geographical names used in Russian texts. The usage of some Lithuanian place-names in all-Union and republican periodicals is being analysed from the point of view of Russian normative grammar. The noted variation in the usage of the borrowed place-names, which undoubtedly requires further investigation, is accounted for by the influence of the source-language.